One-pot mannich base synthesis using task specific protic ionic liquids Sintesis bes mannich tunggal menggunakan cecair ionik terkhusus - Sardar, S. (Malaysian Society of Analytical Sciences, 2017)
Three-component Mannich reaction of ketones, aromatic aldehydes and aromatic amines was catalyzed by four Bronsted acidic ionic liquids comprising of iodide and borate at room temperature. Ionic liquid have been used as catalyst and solvent to produce some Mannich bases in high yield (75) and shorter reaction time (20 minutes). Work up has been facilitated by simple extraction with water to recover ionic liquid for recycling up to four times without any significant loss in activity. © 2017, Malaysian Society of Analytical Sciences. All rights reserved.